An Innovative Approach in Teaching Indonesian - Nur Asia Labuk; Ahmad Syagif; Trimansyah Trimansyah (FASHLUNA, 2026)
This study aims to improve the reading ability of second-grade students at SDN 10 Penatoi through the implementation of a word-arranging game technique in Indonesian language learning. The research employed a Classroom Action Research (CAR) design consisting of two cycles, each including planning, action, observation, and reflection stages. The subjects of this study were 18 students. Data were collected through observation sheets and reading performance assessments. The results showed a significant improvement in students’ reading ability across the cycles. The average score increased from 2.78 in the pre-cycle (low category) to 3.00 in Cycle I (moderate category), and further improved to 3.67 in Cycle II (good category). The total score also increased from 50 in the pre-cycle to 54 in Cycle I, and reached 66 in Cycle II. In addition, most students demonstrated gradual individual progress, with several students achieving the maximum score in the final cycle. These findings indicate that the word-arranging game technique is effective in enhancing students’ reading skills. The interactive and engaging nature of the activity encourages active participation, improves motivation, and facilitates better understanding of word structures. Therefore, this technique can be considered a practical and effective alternative strategy for improving early reading skills in elementary school students.